Influencia del estado nutricional en el desarrollo motor de niños de 0 a 3 años de edad del CNH Gotitas de Miel, Babahoyo - Los Ríos. Diciembre 2022 - mayo 2023. - Mendoza Santos, Denisse Andreina (2023)
Nutritional status is a key element for good motor development in children, since it will allow us to identify any nutrient deficits in children's diets. The objective of this study is to determine the influence of nutritional status on the motor development of children from 0 to 3 years of age from the CNH Gotitas de Miel, Babahoyo - Los Ríos. December 2022 - May 2023. The methodology used was inductive because first the nutritional status is assessed, then motor development is studied and then how one variable influences the other is related. His sample included a group of 45 children from 0 to 3 years of age belonging to the CNH Gotitas de miel child development center. As a technique we used the observation technique and reference patterns of the MSP and the Nelson Ortiz scales were applied. The results showed that according to weight/age, 2.22% have a high weight, 4.45% have a low weight and 93.33 have a normal weight for their age. In the height/age indicator, 2.22% of children have short stature, 2.22% have tall stature and 95.56% have normal height for age. Regarding the BMI/age indicator, 6.67% are overweight, 6.67% are emaciated and 86.66% are normal. In the PC/age indicator, all the children presented normal values. The results in the motor development of children from 0 to 3 years of age of the CNH Gotitas de Miel which gave us as a result that 8.9% of children have a delay in gross motor development and 20% have a delay in fine motor development. Nutritional advice was proposed to publicize the essential nutrients that help to better develop motor skills, since in this way information can be provided about the foods that contain these nutrients and, in this way, mothers can feed their babies correctly. their children. Analyzing the results obtained, it is concluded that there is no influence of nutritional status on motor development since the test is not statistically significant, giving values greater than 0.05.